Antifungal metabolites of biocontrol stain LB-1 and their inhibition mechanism against Botrytis cinerea - Zhang, Huan; Ji, Hongliang; Liu, Caiyun (Frontiers in Microbiology, 2024)
Chaetomium subaffine LB-1 is a novel biocontrol strain which produces non-volatile metabolites that inhibit the growth of Botrytis cinerea. However, the specific metabolites and antimicrobial mechanism of the strain LB-1 remains unclear. In this study, the antifungal substances produced by stain LB-1 as well as the underlying mechanism of its inhibitory effect against B. cinerea were explored using metabolomic and transcriptomic analysis. Results found that 45 metabolites might be the key antifungal substance such as ouabain, ferulic acid, chlorogenic acid, spermidine, stachydrine, and stearic acid. The transcriptomic analysis indicated that the inhibition effect of LB-1 on B. cinerea resulted in up-regulation of genes related to ABC transporters, peroxisome, ER stress, and multiple metabolic pathways, and in down-regulation of many genes associated with the synthesis of cell walls / membranes, carbohydrate metabolism, cell cycle, meiosis, and DNA replication. These results suggested that the inhibitory effect of strain LB-1 against B. cinerea might be due to the destroyed cell wall and membrane integrity exerted by antimicrobial substances, which affect cell metabolism, and inhibits cell proliferation.